Double Cathode Modification Improves Charge Transport and Stability of Organic Solar Cells - Tao Lin; Tingting Dai (Energies, 2022)
Introducing a cathode modification layer is an effective method to obtaining highly efficient organic solar cells (OSCs) and improving their stability. Herein, we innovatively introduced a double cathode modification layer (SnO2/ZnO) into a non-fullerene OSCs based on PM7:IT-4F and explored the mechanisms. The effects of SnO2/ZnO film on charge carriers transfer in OSCs are studied via a variety of electrical testing methods including Photo-CELIV measurements. As a result, a cathode buffer layer with low recombination rate and high carrier mobility could be introduced, which is beneficial to electron transport and collection. The champion device based on the double cathode modification layer acquires an efficiency of 12.91%, obviously higher than that of the single cathode modification layer (SnO2 or ZnO) device. Moreover, The SnO2/ZnO double layer is demonstrated to be of great help in the improvement of device stability, and our work could provide a new inspiration for the preparation of OSCs cathode modification layer.